Proceedings of the 2015 2nd International Conference on Machinery, Materials Engineering, Chemical Engineering and Biotechnolog 2016
DOI: 10.2991/mmeceb-15.2016.24
|View full text |Cite
|
Sign up to set email alerts
|

Influence of super-fine fly ash on the properties of concrete under steam curing condition

Abstract: The mechanical properties and durability of concrete with or without ultrafine fly ash were studied by measuring the compressive strength and determining the chloride ion penetration and open porosity of concrete. The results show that the addition of ultrafine fly ash reduces the compressive strength at 1 day and can significantly improve the compressive strength of concrete at later ages. The durability of concrete can be enhanced by the using of ultrafine fly ash and lowering the W/B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Reported results on the effect of steam curing on properties of concrete containing ultrafine fly ash and high‐volume fractions of ordinary fly ash are very limited. Feng et al reported improvement in compressive strength and other properties of steam‐cured concrete containing ultrafine fly ash at 20% by weight of cement. The concrete containing finer fly ash exhibited higher compressive strength than the control concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Reported results on the effect of steam curing on properties of concrete containing ultrafine fly ash and high‐volume fractions of ordinary fly ash are very limited. Feng et al reported improvement in compressive strength and other properties of steam‐cured concrete containing ultrafine fly ash at 20% by weight of cement. The concrete containing finer fly ash exhibited higher compressive strength than the control concrete.…”
Section: Introductionmentioning
confidence: 99%